Model Pemberdayaan Masyarakat Desa dalam Pembangunan Destinasi Wisata - Muhammad Yusril Indra Syahputra; Ilbasit Taqiyah (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Village community empowerment is an important key in the development of sustainable tourism destinations. This research aims to analyze the community empowerment model of South Pringgasela Village, East Lombok in the development of local tourist attractions. This research uses descriptive qualitative methods with research subjects including tourism village managers and tourists. Data collection techniques were carried out through observation, in-depth interviews, and documentation related to tourism potential and socio-economic conditions of the community. The results showed that South Pringgasela Village has various natural and cultural tourism potentials that are managed participatively by the community through training and empowerment. The village community is very enthusiastic and open in receiving science and technology, especially related to the tourism sector. This has an impact on increasing community income and welfare. However, uncontrolled tourism activities also have a negative impact on the environment, such as pollution, habitat destruction, and increased waste. In addition, tourism development in villages is still faced with limited tourism infrastructure. For this reason, government support is needed in improving promotion, facilities, and multi-stakeholder involvement to make tourism villages a sustainable tourist destination.